2011
DOI: 10.4111/kju.2011.52.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Anatomical Prostate Models for Surgical Skills Workshops Using Ballistic Gelatin for Nerve-Sparing Radical Prostatectomy and Fruit for Simple Prostatectomy

Abstract: PurposeUnderstanding of prostate anatomy has evolved as techniques have been refined and improved for radical prostatectomy (RP), particularly regarding the importance of the neurovascular bundles for erectile function. The objectives of this study were to develop inexpensive and simple but anatomically accurate prostate models not involving human or animal elements to teach the terminology and practical aspects of nerve-sparing RP and simple prostatectomy (SP).Materials and MethodsThe RP model used a Foley ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…By comparison, current ex vivo models for minimally invasive radical prostatectomy training are mainly tissue‐based , and have mainly focused only on practising UVA or nerve‐sparing components . Alemozaffar et al presented the only procedural tissue‐based simulator similar to our platform that allows the practice of NS‐RARP in sequential fashion.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, current ex vivo models for minimally invasive radical prostatectomy training are mainly tissue‐based , and have mainly focused only on practising UVA or nerve‐sparing components . Alemozaffar et al presented the only procedural tissue‐based simulator similar to our platform that allows the practice of NS‐RARP in sequential fashion.…”
Section: Discussionmentioning
confidence: 99%
“…A gelatin phantom which mechanically mimics the prostatic tissue was used to validate the proposed framework. Such material has been widely used for surgical training [25] and ultrasound diagnosis [26] for prostate. To make the phantom materials, gelatin powder was mixed with boiling water (144 g/l for "cancerous" and 120 g/l for 'healthy' samples) and the cancerous sample was dyed Fig.…”
Section: Materials Characterization Of Gelatin Phantommentioning
confidence: 99%
“…However, it can be difficult to achieve high fidelity simulation creating complex clinical scenarios, while controlling and testing the many possible variables [35]. Despite this challenge, inexpensive, relatively high fidelity technical models have been developed for pyeloplasty and radical prostatectomy [36,37]. Similarly, Brewin et al [33] demonstrated that full immersion simulation via distributed simulation environment using a portable inflatable 360°e nclosure, facilitated technical and non-technical learning in a relatively cost-effective manner.…”
Section: Types Of (Technical Simulators)mentioning
confidence: 99%
“…3 Building simulation modules around the three fundamental categories of open, laparoscopic/robotic and endoscopic surgery. 4 Looking for reusable or inexpensive items to build models such as those described for pyeloplasty and radical prostatectomy [36,37]. 5 Utilising resources that are not obvious such as butcher shops and industrial shops for thrown away materials, cheap tooling or machining needs.…”
Section: Proposed Approachmentioning
confidence: 99%